Investigating popular fiction development at the University of the Free State academic Library - Maphile, Legopheng Marcus (Library and Information Studies Centre (LISC), 2021)
The study seeks to find out students' and library staff's perceptions and experiences of the popular fiction collection at the University of the Free State's Sasol Library. The purpose of the study is to examine what these perceptions and experiences mean for the future expansion and development of the leisure collection. The Social Learning Theory guided the study. The study adopted a qualitative and quantitative approach whereby open- and close-ended questionnaires were distributed online to students and to library staff to gather research data. The population that participated in the study comprised undergraduate and postgraduate students and library staff. The study employed stratified random sampling as a research technique. The targeted population comprised 37,800 registered students and 61 library staff members accidentally sampled. This in turn gave sample sizes of 381 for students and 53 for library staff. Quantitative data was analysed using Google Forms and the Statistical Package for the Social Sciences (SPSS). Further, qualitative data was analysed thematically through content analysis. The study found that students enjoy reading popular fiction at the Sasol Library's fiction collection for leisure. The study also found that library staff support the existence of the leisure reading collection, even though a small number felt that its operations could be improved. The study therefore recommends that the university direct resources towards the expansion and improvement of the popular collection through the training of staff and stocking of reading genres that the students require.